2020
DOI: 10.1155/2020/1438928
|View full text |Cite
|
Sign up to set email alerts
|

Development of Human Vectored Brucellosis Vaccine Formulation: Assessment of Safety and Protectiveness of Influenza Viral Vectors Expressing Brucella Immunodominant Proteins in Mice and Guinea Pigs

Abstract: In this paper, we first used recombinant influenza viral vector (rIVV) subtype H5N1 expressing from the open reading frame of NS1 80 and NS1 124 amino acids of Brucella outer membrane proteins (Omp) 16 and 19, ribosomal L7/L12, and Cu-Zn superoxide dismutase (SOD) proteins to develop a human brucellosis vaccine. We made 18 combinations of IVVs in mono-, bi-, and tetravalent vaccine formulations and tested them on mice to select the safest and most effective vaccine samples. Then, the most effective vaccine can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…After immunization with recombinant influenza A viruses of the subtypes H5N1 and H1N1 expressing Brucella protective antigen (ribosomal protein L7/L12 or Omp16), a strong cellular immune response and protective effect were induced, even comparable with those induced by a commercial B. abortus S19 vaccine [180] . Further, a tetravalent vaccine formulation (expressing Omp16, L7/L12, Omp19, and Cu-Zn SOD in recombinant influenza viral vector subtype H5N1 without an adjuvant) was developed to prevent human brucellosis [181] , [240] . In addition, because Brucella can infect people of any age, the long-term protection of this viral vector vaccine also needs to be considered.…”
Section: Bacterial Infectious Diseases and Advanced Delivery Systemsmentioning
confidence: 99%
“…After immunization with recombinant influenza A viruses of the subtypes H5N1 and H1N1 expressing Brucella protective antigen (ribosomal protein L7/L12 or Omp16), a strong cellular immune response and protective effect were induced, even comparable with those induced by a commercial B. abortus S19 vaccine [180] . Further, a tetravalent vaccine formulation (expressing Omp16, L7/L12, Omp19, and Cu-Zn SOD in recombinant influenza viral vector subtype H5N1 without an adjuvant) was developed to prevent human brucellosis [181] , [240] . In addition, because Brucella can infect people of any age, the long-term protection of this viral vector vaccine also needs to be considered.…”
Section: Bacterial Infectious Diseases and Advanced Delivery Systemsmentioning
confidence: 99%
“…In addition, it does not present any serious risk to human health ( Ferko et al., 2004 ) unlike other commercial Brucella vaccines ( Spink et al., 1962 ; Beckett and MacDiarmid, 1985 ; Schurig et al., 1991 ). This is evidenced by the fact that research is currently under way using IVV platform to develop a brucellosis vaccine for humans ( Bugybayeva et al., 2020 ; Bugybayeva et al., 2021 ). Another important advantage of Flu-BA vaccine is that it is in line with the DIVA strategy, which allowed B. abortus RB-51 to virtually replace the earlier B. abortus S19 vaccine from the market.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern is related to the interspecies transmission of the disease from birds to humans, which could lead to human disease. Although the replication capacity of this virus has been limited in this vaccine by eliminating the proteolytic cleavage site in HA, the risk of pandemic strains must be considered ( 52 ). Lactic acid bacteria (LAB) are also considered a desirable antigen delivery system for mucosal immunization.…”
Section: Vector Vaccinesmentioning
confidence: 99%
“…The results of this study indicated that this formulation had a high level of safety and efficacy. This research is an important report on the development of a safe and protective vaccine against human brucellosis ( 52 ). In another study, recombinant influenza A viruses of the subtypes H5N1 and H1N1, expressing L7/L12 or Omp16, were developed and shown to elicit Th1 CD4 + and CD8 + T-cell immune responses and confer good protection against challenge ( 61 ).…”
Section: Vector Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation